Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD): the interplay of gut microbiome, insulin resistance, and diabetes - Ankita Dua; Rashmi Kumari; Mona Singh; Roushan Kumar; Sunila Pradeep; Sunila Pradeep; Akinyemi I. Ojesina; Akinyemi I. Ojesina; Akinyemi I. Ojesina; Roshan Kumar; Roshan Kumar; Roshan Kumar (Frontiers in Medicine)
The global prevalence of Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD) has reached alarming levels, affecting nearly one-third of the world's population. This review analyzes current evidence on the intricate relationships between MASLD, insulin resistance, and type 2 diabetes mellitus (T2DM), with particular emphasis on gut microbiome interactions. As MASLD progresses from simple steatosis to Metabolic Dysfunction-Associated Steatohepatitis (MASH), it can lead to severe complications including fibrosis, cirrhosis, and hepatocellular carcinoma. The pathogenesis of MASLD is multifactorial, involving hepatic lipid accumulation, oxidative stress, inflammation, and dysregulation of the gut-liver axis. Insulin resistance is a central driver of disease progression, closely linked to obesity and metabolic syndrome. Recent research highlights how gut microbiome dysbiosis exacerbates MASLD through mechanisms such as increased intestinal permeability, systemic inflammation, and altered metabolic signaling. Identification of microbial signatures offers promise for novel diagnostic and therapeutic strategies. By integrating metabolic, inflammatory, and microbial perspectives, this review provides a comprehensive overview of MASLD pathogenesis and its association with obesity, insulin resistance, and T2DM.